Odpowiedź :
a) 2x-y=5
2x=5+y/2
x=(5+y)/2
b) 1/3y=x-3/3
y=3x-9
3x=-9-y/:3
x=-3-1/3y
c) 3(x-y)=2x
3x-3y=2x
x=3y
d) 2/3x=3/4y/*12
8x=9y/:8
x=9/8y
e) 4x+2y=1
4x=1-2y/:4
x=1/4-1/2y
f)6x-2/3y=2/*3
18x-2y=6
18x=6+2y/:18
x=1/3+1/9y
2x=5+y/2
x=(5+y)/2
b) 1/3y=x-3/3
y=3x-9
3x=-9-y/:3
x=-3-1/3y
c) 3(x-y)=2x
3x-3y=2x
x=3y
d) 2/3x=3/4y/*12
8x=9y/:8
x=9/8y
e) 4x+2y=1
4x=1-2y/:4
x=1/4-1/2y
f)6x-2/3y=2/*3
18x-2y=6
18x=6+2y/:18
x=1/3+1/9y
2x - y = 5 / + y
2x = 5 + y / ÷2
x = (5 + y) ÷ 2
1/3y = x - 3 / +3
1/3y + 3 = x
x = 1/3 + 3
3(x-y) = 2x
3x - 3y = 2x / -(2x)
x - 3y = 0 / +(3y)
x = 3y
2/3x = 3/4y / ÷(2/3)
x = (3/4y) ÷ 2/3
4x + 2y = 1 / - (2y)
4x = 1 - 2y / ÷ 4
x = (1 - 2y) ÷ 4
6x - 2/3y = 2 / +2/3y
6x = 2 +2/3y / ÷ 6
x = (2 +2/3y)÷6
2x = 5 + y / ÷2
x = (5 + y) ÷ 2
1/3y = x - 3 / +3
1/3y + 3 = x
x = 1/3 + 3
3(x-y) = 2x
3x - 3y = 2x / -(2x)
x - 3y = 0 / +(3y)
x = 3y
2/3x = 3/4y / ÷(2/3)
x = (3/4y) ÷ 2/3
4x + 2y = 1 / - (2y)
4x = 1 - 2y / ÷ 4
x = (1 - 2y) ÷ 4
6x - 2/3y = 2 / +2/3y
6x = 2 +2/3y / ÷ 6
x = (2 +2/3y)÷6
a) 2x-y=5
2x=5+y
x=5+y/2
b)1/3y=x-3
x=1/3y+3
c)3(x-y)=2x
3x-3y=2x
3x=2x+3y
x=3y
d)2/3x=3/4y
x=9/8y
e)4x+2y=1
4x=1-2y
x=1/4-1/2y
f)6x-2/3y=2
6x=2+2/3y
x=1/3+1/9y
2x=5+y
x=5+y/2
b)1/3y=x-3
x=1/3y+3
c)3(x-y)=2x
3x-3y=2x
3x=2x+3y
x=3y
d)2/3x=3/4y
x=9/8y
e)4x+2y=1
4x=1-2y
x=1/4-1/2y
f)6x-2/3y=2
6x=2+2/3y
x=1/3+1/9y